Male Circumcision: A Means to Reduce HIV Transmission between Truckers and Female Sex Workers in Kenya - Kimulu, Ancent M; Mutuku, Winifred N; Mwalili, Samuel M (My University, 2022)
Kenya records over 1.5 million cases of HIV-infected people with a prevalence of 4.8% among adults in 2019, ranking Kenya as the seventh-largest HIV population in the world. A recent study showed that 55.9% of Kenyan truckers pay for sex in while 46.6% had a regular partner along their trucking route in addition to a wife or girlfriend at home. The complexity in the sexual network of Truckers, which can be a conduit for the widespread of HIV, necessitated the need to better understand the dynamics of transmission of HIV/AIDS between truckers and female sex workers. In this study, a model is formulated for HIV/AIDS dynamics along the Northern corridor highway in Kenya. The reproduction number, disease-free equilibrium and endemic equilibrium points were determined and their stabilities were also determined using the next generation matrix method. The disease-free equilibrium is stable when R0u < 1, R0c < 1 and R0f < 1 while the endemic equilibrium point is stable when R0u > 1, R0c > 1 and R0f > 1. It is found that circumcision can be used as an intervention to minimize the infection of HIV among truckers and female sex workers.
Keywords: HIV/AIDS dynamics; truckers; female sex workers (FSW); male circumcision